Romania : Financial Sector Assessment Program-Technical Note-Systemic Risk Analysis and Stress Testing the Financial Sector. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Note discusses the results of systemic risk analysis and stress testing of Romania's financial sector. Although the Romanian banking sector has a strong initial capital position, banks are affected significantly by the realization of the shocks captured by the scenarios. The stress test results indicate that an extreme but plausible adverse scenario would have a significant negative impact on the capital ratios of the banking system. Although the banking sector as a whole maintains capital ratios above the minimum regulatory requirements, several (smaller) banks prove vulnerable. The extreme adverse scenario reflects downside external risks as well as a domestic demand shock impacting private consumption and investment.